Enantiospecific Synthesis of ortho‐Substituted 1, 1‐Diarylalkanes by a 1, 2‐Metalate Rearrangement/anti‐SN2′ Elimination/Rearomatizing Allylic Suzuki–Miyaura Reaction Sequence. (21st December 2018) - Rubial, Belén; Collins, Beatrice S. L.; Bigler, Raphael; Aichhorn, Stefan; Noble, Adam; Aggarwal, Varinder K.
Abstract: The one‐pot sequential coupling of benzylamines, boronic esters, and aryl iodides has been investigated. In the presence of an N‐activator, the boronate complex formed from an ortho ‐lithiated benzylamine and a boronic ester undergoes stereospecific 1, 2‐metalate rearrangement/anti‐SN 2′ elimination to form a dearomatized tertiary boronic ester. Treatment with an aryl iodide under palladium catalysis leads to rearomatizing γ‐selective allylic Suzuki–Miyaura cross‐coupling to generate 1, 1‐diarylalkanes. When enantioenriched α‐substituted benzylamines are employed, the corresponding 1, 1‐diarylalkanes are formed with high stereospecificity.